PENGARUH MEDIA TANAM TERHADAP KEBERHASILAN SETEK BATANG ROMBUSA PUTIH (Tabernaemountana coryimbusa) - NUR KHOLIS; Sarbino Sarbino; Agus Hariyanti (Jurnal Sains Pertanian Equator, 2018)
INFLUENCE OF PLANTING MEDIA ON THE SUCCESS OF WHITE ROMBUSASTEM   CUTTINGS(Tabernaemontana coryimbusa)Nurkholis1, Sarbino2, Agus Hariyanti3 1Agriculture; Faculty University of Tanjungpura2Agriculture; Faculty University of Tanjungpura3Agriculture; Faculty University of Tanjungpurae-mail*nurkholis_h@ymail.com ABSTRAKWhite rombusa is an ornamental plant that has a green-white leaf pattern as well as beautiful flowers with white color and has five crowns resembling a ship's propeller with the bottom shaped like a small pipe. This study aims to determine the effect of planting media on the success of  white rombusa stem cuttings and get the best planting media. The research was conducted at Bening Multi Flora Garden of Ampera Kota Baru Pontianak from March 30 - May 10, 2017. The design used Completely Randomized Design with treatment m1 = PMK soil (kontrol),  m2 = PMK soil andcharcoal husk(1:1), m3 = PMK soil andcow manure(1:1),        m4 = PMK soil and charcoal husk(2:1), m5 = PMK soil and cow manure(2:1),  m6 = PMK soil, charcoal husk, and cow manure. Observation parameters Percentage of live cuttings (%), Leaf emeration time (days), Number of shoots (fruit), Number of leaves (length), (cm), Root length (cm). Planting medium has an effect on to success of stem of  white rombusa and treatment PMK soil and cow manure (1:1) gives the best influence to the success percentage variable of live cut 70,85, Number of shoots 3,25,Number of leaves 8,00, Shoot length 6,05 and Root lengt 5,05 compared with other treatment. Keywords: Charcoal Husk, Cow Manure, Soil PMK